Analysis Of The Needs Of Iain Curup Lecturer And Educational Personnel To Create Happiness In The Workplace - Dewi Purnama Sari; Sutarto Sutarto; Hamengkubuwono Hamengkubuwono (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This qualitative research with a phenomenological approach aims to analyze the needs of IAIN Curup lecturers and educational staff related to the hope of realizing happiness in the workplace. Research informants consisted of 149 lecturers and 59 educational staff. The data collection technique used semi-structured interviews and analyzed using thematic analysis, then checking the validity of the data using source triangulation. Based on the research results, it is known that in order to create happiness in the workplace, lecturers and educational staff at IAIN Curup expect improvement, maintenance, and arrangement of workplace facilities and environment, attention and support from leadership, clear SOPs for work, provision of rewards and openness in work.